2008
DOI: 10.1021/jp807598w
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Reaction of CH2(X3B1) with CH3OH

Abstract: The reaction of triplet methylene with methanol is a key process in alcohol combustion but surprisingly this reaction has never been studied. The reaction mechanism is investigated by using various high-level ab initio methods, including the complete basis set extrapolation (CBS-QB3 and CBS-APNO), the latest Gaussian-n composite method (G4), and the Weizmann-1 method (W1U). A total of five product channels and six transition states are found. The dominant mechanism is direct hydrogen abstraction, and the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Finally, we explored a pathway motivated by the result, shown in Table , that C−O bond activation in CH 2 OH has a relatively small barrier. This result led us to explore a DME formation pathway through CH 3 OCH 2 ; this is a known radical and has been shown to be a viable pathway in past . We find, however, the energy barrier for the rate limiting step of CH 3 OCH 2 formation to be quite high (1.89 eV).…”
Section: Resultsmentioning
confidence: 82%
“…Finally, we explored a pathway motivated by the result, shown in Table , that C−O bond activation in CH 2 OH has a relatively small barrier. This result led us to explore a DME formation pathway through CH 3 OCH 2 ; this is a known radical and has been shown to be a viable pathway in past . We find, however, the energy barrier for the rate limiting step of CH 3 OCH 2 formation to be quite high (1.89 eV).…”
Section: Resultsmentioning
confidence: 82%
“…One can see that all six reaction channels involve significant barriers, so the variational effects might be negligible. 43 The conventional TST is employed. The detailed rate constants with the temperature for (R1)-(R6) are given in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…So the TST can give reliable results based on little information, especially when the tunneling and variational effects are negligible. One can see that all six reaction channels involve significant barriers, so the variational effects might be negligible . The conventional TST is employed.…”
Section: Resultsmentioning
confidence: 99%
“…however, it is confirmed that difference of the magnitude of the rate parameters does not influence the evolution of [H] too much.Contribution of dehydration reaction of CH 3 OH by CH 2 may be one of the unique features of the CH 3 OH kinetic process 3. CH 2 + CH 3 OH reaction 17 was studied theoretically by Li et al26 This theoretical study suggests that the main product of reaction 17 is CH 3 + CH 3 O; this is in distinct contrast to the other dehydration reactions, eqs 11−16, 19, and 20, and the kinetic parameter fitted to this theoretical result is employed in the present model; however, the 1 CH 2 + CH 3 OH reaction, reaction 18, may dominate in the entire reactions of CH 2 + CH 3 OH at high temperature range, and the contribution of reaction 17 in the oxidation process may be minor. Although the estimated rate by Tsang 27 is much lower than that given by Li et al, the evolutions of [H] calculated by using these two rates do not show clear difference each other.…”
mentioning
confidence: 99%